ULTRAVIOLET SPECTRUM VARIABILITY OF BP TAU - Ismailov, N. Z.; Alimardanova, F. N.; Baheddinova, G. R.; Adygezalzade, H. N. (Одеські астрономічні публікації, 2010)
Results of the ultraviolet IUE archive spectrum researches of classic T Tauri type star BP Tau had been presented. Spectroscopic parameters of mainly strong emission lines were measured. On the more full massive which had been created on the intensity values of the emission doublet MgII λ 2800Å a variability with period P = 8.275 ± 0.005 days with high confidence level was obtained. There is some group of lines, intensities of emission lines for which were showed decreasing for more than 13 years of time interval. As a rule, lines with high potential of excitation related to the first group. More probable, such lines shows periodic variability. It is showed that we have as a minimum two local physical conditions of matter in the circumstellar disk of the star.